The Post-pandemic MICE digitalization development: A strategy for sustainable tourism in Bali - Dewi, Ni Made Rosita; Darma, Gede Sri (International Journal of Applied Sciences in Tourism and Events, 2024)
The worldwide COVID-19 pandemic has forced numerous businesses to a standstill, with the tourism sector, especially the Meetings, Incentives, Conferences, and Exhibitions (MICE) sector, facing severe challenges. However, this unprecedented situation highlights the unpredictable nature of crises and their potential to reshape travel patterns. This research examines the factors contributing to the success of the digitalization strategy in the MICE industry and explores the impact of digitalization on the industry's pursuit of sustainable tourism goals. The research employs a detailed and all-encompassing examination of the subject, utilizing a case study research methodology in conjunction with a qualitative descriptive research strategy. Data collection involves observation, literature analysis, and interviews conducted with participants in the tourism industry and management of MICE companies. The findings suggest significant potential for Bali as a MICE destination. Digitalization is identified as a pivotal factor in enhancing the future resilience of the MICE industry by creating new prospects, tackling industry challenges, and promoting sustainable event tourism.